Investigation on Seismic Performance of Bidirectional Self-Centering Reinforced Concrete Frame Structures by Shaking Table Tests - Zhenying Wang; Chenxi Mao; Lili Xie (Shock and Vibration)
This paper presents an experimental study on the seismic performance of a bidirectional self-centering reinforced concrete (RC) frame structure. In the structure, the column-base joints, which were installed with external mild steel (MS) dampers, could uplift freely and the beam-column joints could open effectively under earthquake excitations. Angle steels and MS dampers were installed at the beam-column joints in the structural X and Y directions, respectively. During the gap opening of the joints, unbonded posttensioned (PT) steel wires, which passed through the plastic ducts inserted in the RC beams and columns, provided the structure with the ability to return to pre-earthquake positions, and the yielding MS dampers and angle steels dissipated the seismic energy. A 1/2-scale two-story model structure was designed and constructed. Shaking table tests were performed on the structure under four different types of earthquake excitations with increasing seismic hazard levels. The test results indicated that the self-centering RC frames installed in both the directions showed satisfactory seismic performance, with only slight damage to the main structure after extreme earthquakes. The natural frequencies of the self-centering frames installed in both the directions degraded progressively, mainly because of the prestress loss of the PT steel wires and the yielding of the MS dampers. The structure showed desirable self-centering ability with very small residual deformation under ground motions of all hazard levels. The structural deformation was mainly concentrated at the column-base and beam-column joints, and hence, damage to the concrete beams and columns was considerably alleviated. In addition, the residual gap opening of the joints was minimal.